Три новых вида рода Idris (Hymenoptera, Scelionidae) из Болгарии - Кононова, С.В.; Петров, С. (Вестник зоологии, 1993)
Three new species of scelionids are described: Idris tenerum, I. purum, I. latus. Their comparative / morphological characteristics are given Holotypes are presented in collection of the Institute of Zoology of Ukraine (Kiev)